Hukum Tata Negara atas Pembatalan Revisi UU Pilkada - Esti Ningrum (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
The Regional Head Elections (Pilkada) serve as a profound expression of direct democracy, empowering citizens with the responsibility to select their local leaders. Nevertheless, the amendment of Law No. 10 of 2016 pertaining to Pilkada frequently incites debate, particularly in relation to the criteria for nominations and the requisite support threshold. This analysis seeks to examine constitutional law through the lens of the interaction between the Constitutional Court and the DPR regarding the annulment of the Pilkada Law revision. The proposed revision of the Pilkada Law by the DPR in August 2024 is intricately connected to the ruling of the Constitutional Court. This research methodology employs a normative legal framework, grounded in primary legal texts including Constitutional Court rulings and statutory regulations, alongside secondary scholarly literature. The findings of the study indicate that the DPR's failure to adhere to the Constitutional Court's ruling undermines the supremacy of the constitution and disturbs the equilibrium of checks and balances among state institutions. The ramifications of the annulment of this revision result in the 2024 Pilkada adhering to the extant provisions set forth by the Constitutional Court; however, it engenders a climate of uncertainty within the legislative process and diminishes public confidence in the legal framework. This study's originality is rooted in its comprehensive examination of the interplay between legislative and judicial institutions within the framework of Pilkada policy formation, a topic that is seldom explored in the realm of constitutional law. This research offers a fresh viewpoint on the legal and political ramifications stemming from the DPR's disregard for the Constitutional Court's ruling. Nonetheless, this study presents certain limitations as it concentrates solely on the normative dimension, neglecting to examine the political dynamics and interests of the stakeholders involved in the amendment of the Pilkada Law. Furthermore, this study has yet to investigate the enduring effects on the democratization process and the legal stability within Indonesia.